Pengaturan Kondisi Kelas Dan Iklim Belajar di IV SD Muhammadiyah Alternatif 2 Kota Magelang - Vidya Puspita Rani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to observe, observe how the implementation of classroom management inSD Mutual 2 Magelang City. The research method used is a qualitative method withobservations and interviews in the school environment. The results of this study indicatethat the classroom management at SD Mutual is very good, with neatly arranged roomsand decorations that make children enthusiastic about learning. The implementation inmanaging classes in schools is by making the class full of student work, prioritizing studentactivity during the teaching and learning process, using a skills approach in learning sothat students can master skills in managing the class, by rolling out student seatingarrangements who are already able mastering learning is moved to the back seat whilestudents who have not mastered learning are moved to sit in the front to focus more on thematerial being conveyed, create learning media from student skills and students who worktogether to achieve learning goals that create a classroom atmosphere and atmospherelearning to be fun and conducive.